1999
DOI: 10.1088/0953-2048/12/3/007
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and study of the ceramic high- superconductor (, 0.5, 0.7, 0.9 and 1)

Abstract: High- superconducting ceramic samples of the form (x = 0.3, 0.5, 0.7, 0.9 and 1) are prepared in a closed quartz tube at C. The electrical resistance versus temperature is measured in the temperature range between 15 K and room temperature. The effect of magnetic field and applied electric current on the second stage of the transition is studied. It is found that the transition does not occur at a definite temperature but in a temperature range which may approach 50 K or even more. This is believed to be due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…From these results we can conclude that the decoupling temperature "T d " is less than 111 K. The overlapping of magnetoresistance curves at 111 K is due to the absence of flux trapped (above the knee), which hints that vortex pinning may be ineffective at elevated temperatures. These results are consistent with our previous results for (Hg, T1)-1223 [6], (T1, In)-1223 [7] and (Tl, In)-1212 [18] which showed that both driving currents and magnetic field are ineffective at the first stage of transition and enlarged the transition width in the second stage of transition. Also, these data could contain some information concerning the special distribution of the "strong" superconducting grains and "weak" superconducting boundaries.…”
Section: Fig (1)supporting
confidence: 93%
See 1 more Smart Citation
“…From these results we can conclude that the decoupling temperature "T d " is less than 111 K. The overlapping of magnetoresistance curves at 111 K is due to the absence of flux trapped (above the knee), which hints that vortex pinning may be ineffective at elevated temperatures. These results are consistent with our previous results for (Hg, T1)-1223 [6], (T1, In)-1223 [7] and (Tl, In)-1212 [18] which showed that both driving currents and magnetic field are ineffective at the first stage of transition and enlarged the transition width in the second stage of transition. Also, these data could contain some information concerning the special distribution of the "strong" superconducting grains and "weak" superconducting boundaries.…”
Section: Fig (1)supporting
confidence: 93%
“…Generally, Tl-1223 phase was reported for the two compositions TlBa 2 Ca 2 Cu 3 O 9-δ [2] and (Tl 0.5 Pb 0.5 )Sr 2 Ca 2 Cu 3 O 9-δ [4]. The substitutions of Hg, Y [5,6] and In [7] into Tl-sites in the TlBa 2 Ca 2 Cu 3 O 9-δ were studied. They found that a small addition of Hg enhances the transition temperature from 122 K to 131 K whereas the addition of In reduces the transition temperature from 122 K to 100 K. Also, (Tl 0.5 Pb 0.5 ) Sr 2 Ca 2 Cu 3 O 9-δ can be improved by partial substitution of Ba +2 into Sr +2 sites and Tl by Pb and Bi [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, an amount of flux is trapped. As a result, the strength of the vortex pinning is weakened and the specimen is in a more resistive state [25]. The second one is that T decreases as the Sc content increases until x = 0.05 and then it increases.…”
Section: Resultsmentioning
confidence: 98%
“…Arrhenius law can be used to determine the activation energy of a superconductor in the low resistance region. According to the Equation () derived from the Equation (), the activation energy in the various applied magnetic fields can be computed from the slope of the linear part in the expanding tails of the Arrhenius plots: 24 ρT,H=ρ0expU0true/kBT,U0=kBTlnρρ0,where ρ ( T , H ) is the resistivity value of the samples at temperature T and magnetic field H , ρ 0 is the pre‐exponential factor independent of the field, k B is the Boltzmann constant and U 0 is the activation energy. The ln ( ρ / ρ 120 K ) − 1/ T Arrhenius graphs obtained from Figure 2 are shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%